PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP DISIPLIN KERJA (Studi Kasus Pada Usaha Tenun Dan Batik Toraja di Magelang) - Leonita Biovani Pertis Bata; Ari Pradhanawati (Universitas Diponegoro, 2019)
This study aims to determine leadership, organizational culture and employee work discipline in Toraja Weaving and Batik Business in Magelang and obtain empirical evidence of the influence of organizational leadership and culture on employee work discipline in Toraja Weaving and Batik Business in Magelang partially or simultaneously. Population in research this is all employees in the Toraja weaving and batik business in Magelang which is as many as 30 people. Sampling uses saturated sampling techniques so that the entire population becomes a sample. Research data sources use primary data and secondary data. Data collection techniques using interviews, documentation and questionnaires with a measurement scale in the form of linkert scale. Data analysis using multiple regression after fulfilling the test of validity, reliability and classical assumption test. The results showed that leadership, organizational culture were in good criteria and the majority employee work discipline was in high criteria. There is an influence of leadership on employee work discipline with a value of t count = 2.695 and significance = 0.012 <α = 0.05. There is an influence of organizational culture on employee work discipline with t count = 2.189 and significance = 0.037 <α = 0.05. There is a simultaneous influence of leadership and organizational culture on employee work discipline with t count = 10.833 and significance = 0.000 <α = 0.05.